Tetrameric bacterial sodium channels: characterization of structure, stability, and drug binding - Nurani, Ghasem; Radford, Matthew; Charalambous, Kalypso; O'Reilly, Andrias O; Cronin, Nora B; Haque, Sharmeen; Wallace, B A (Biochemistry (Easton), 2008)
NaChBac from Bacillus halodurans is a bacterial homologue of mammalian voltage-gated sodium channels. It has been proposed that a NaChBac monomer corresponds to a single domain of the mammalian sodium channel and that, like potassium channels, four monomers form a tetrameric channel. However, to date, although NaChBac has been well-characterized for functional properties by electrophysiological measurements on protein expressed in tissue culture, little information about its structural properties exists because of the difficulties in expressing the protein in large quantities. In this study, we present studies on the overexpression of NaChBac in Escherichia coli, purification of the functional detergent-solubilized channel, its identification as a tetramer, and characterization of its secondary structure, drug binding, and thermal stability. These studies are correlated with a model produced for the protein and provide new insights into the structure-function relationships of this sodium channel.